Integrating intra- and interpersonal perspectives on chronic low back pain: the role of emotion regulation and attachment insecurity - Yang, Yixin; Mischkowski, Dominik (Frontiers in Psychology, 2024)
Chronic low back pain (CLBP) is burdensome and interferes with the psychological and physical functioning of those affected. Past research has examined interpersonal or intrapersonal factors involved in chronic pain. However, to enhance our understanding of CLBP's biopsychosocial underpinnings, more empirical integration of both intra- and interpersonal factors involved in CLBP is needed. Thus, our study examined the independent and joint associations of insecure attachment dimensions and emotional regulation (ER) strategies with CLBP severity and interference. We recruited 242 US adults with CLBP through Prolific Academic, an online participant pool. Participants were eligible if they were at least 18 years of age, resided in the US, reported CLBP at least half the days over the past 6 months (> 3 months), and used prescribed pain medication for their CLBP. Participants filled out a Qualtrics survey which consisted of measures assessing insecure attachment dimensions, ER strategies, and demographical information. Outcome variables in the present study were CLBP severity and interference. We ran multiple linear regression models to examine the associations among ER strategies, insecure attachment dimensions, and CLBP severity or interference; we also conducted moderation analyses to investigate the interactions between ER strategies and insecure attachment dimensions when testing associations with CLBP severity or interference. Our results indicated that, after controlling for ER strategies, anxious attachment was positively associated with CLBP interference but not pain severity; avoidant attachment was not associated with CLBP interference or severity. After adjusting for anxious and avoidant attachment, emotional expression and expressive suppression were positively associated with CLBP severity but not interference. Furthermore, emotional expression was associated with CLBP severity and interference at low and medium levels of avoidant attachment; expressive suppression and cognitive reappraisal did not interact with attachment dimensions when examining CLBP severity or interference. Our study shows that anxious attachment may be an interpersonal risk factor related to CLBP, above and beyond intrapersonal ERs, as anxious attachment was associated with higher levels of pain interference. Furthermore, emotional expression was associated with increased CLBP severity and interference, particularly among individuals at low and medium levels of avoidant attachment.